Effects of game Kinect Sports on motor learning transfer - Vaghetti, César Augusto Otero; Franco, Vagner Eduardo Hirschfeld; Monteiro-Junior, Renato Sobral (Brazilian journal of physical education and sport, 2023)
There is evidence in the literature that training in a virtual environment can improve motor skills in performing certain tasks. In this sense, the aim of this research was to investigate the influence of the practice of Table Tennis in the game Kinect Sports, on the transfer of learning to Table Tennis. Twenty-eight subjects participated in the research, mean age 21,9 ± 1,9 years. An Xbox 360 console with a Kinect sensor and a Kinect Sports game in Table Tennis mode, a projector, Epson brand, balls, table and table tennis rackets, and EVA targets were used. The adapted Massigli test was used, which requires the subject to perform hitting movements with the table tennis racket trying to hit pre-selected targets on the opposite half of the table. Three game training sessions were performed, separated by a 24-hour interval, during one hour. The test was performed in two moments: before and after the intervention in both groups. For statistical analysis, the Student t test was performed on the delta ∆ (post-test value subtracted from the pre-test value), to identify a possible effect of the intervention. A statistically significant difference was found between groups with p = 0.006. The group that practiced table tennis in a virtual environment improved the performance in the test compared to the group that did not undergo the intervention. It can be concluded that young adult individuals can improve motor tasks in the table tennis game through training in a virtual environment in the game Kinect Sports, on the Xbox 360 console.